Penerapan pendekatan ergonomi total dalam menurunkan kelelahan kerja: Studi literatur - Euis Nina Saparina Yuliani; I Putu Gede Adiatmika; Ketut Tirtayasa; Nyoman Adiputra (Universitas Mercu Buana, 2021)
Work fatigue is one of the factors that affect occupational health and safety. To create a good quality of occupational health, an approach that can be applied to reduce work fatigue is needed, so that good work performance can be achieved. The purpose of this study was to carry out a systematic literature study to determine the application of the Total Ergonomics Approach in reducing worker fatigue. This literature study is useful for explaining the Total Ergonomic Approach model, fatigue measurement instruments, and various improvement interventions carried out in various fields of work. The research method used is a systematic literature study through databases such as Google Scholar, Science Direct, Researchgate, and the Indonesian Scientific Repository-Neliti, using the keywords total ergonomics approach and work fatigue. The Total Ergonomic Approach Model was found to obtain optimal repair solutions, in the fields of industrial work, agriculture, education and hospitality, and others. Improvement interventions developed include improving work attitudes, working conditions, providing nutrition, and redesigning work tools. The measurement of work fatigue in all literature was carried out using a questionnaire instrument. Based on this literature study, there is a research gap to develop a model of a total ergonomics approach in the transportation sector to reduce logistics driver fatigue and to develop an objective and real-time fatigue measurement instrument. So that it can produce a contribution to creating quality health and safety for logistics drivers.